Kinetic liquid metal synthesis of flexible 2D conductive oxides for multimodal wearable sensing - Md Saifur Rahman; Simon A. Agnew; Samuel W. Ong; William J. Scheideler (npj Flexible Electronics)
Abstract Transparent conducting oxides (TCOs) are crucial for high-performance displays, solar cells, and wearable sensors. However, their high process temperatures and brittle nature have hindered their use in flexible electronics. In this paper, we overturn these limitations by harnessing Cabrera-Mott oxidation to fabricate large-area, two-dimensional (2D) transparent electrodes via liquid metal printing. Our robotic, vacuum-free process deposits ultrathin (2–10 nm) indium tin oxide (ITO) with exceptional flexibility, transparency (>95%) and conductivity (>1300 S/cm) by utilizing hypoeutectic In-Sn alloys to print at <140 °C. Detailed characterization reveals the efficacy of Sn-doping and high crystallinity with large, platelike grains. The ultrathin nature enhances bending strain tolerance and scratch resistance, exceeding durability of PEDOT and offering low contact impedance to skin comparable to Ag/AgCl. We implement 2D ITO in synchronous, multimodal electrocardiography (ECG) and pulse plethysmography (PPG) measurements. This order-of-magnitude improvement to printed TCOs could enable wearable biometrics and display-integrated sensors.